(3GdSfZGd hehQjJGfjGs - (3CMeO Hf GdLfjO GdJfOZjs ((3ehQjJGfjG s)
(3ChdgG (B:s
(3hHYO agPg fHPI cJHJgG ai SfcGd hehQJGf hChhLRJ ajgG cd GdEjLGR JcdeJ ajgG Yf GdHdOjf hCgdgeG ELeGdkG Ke Ydi GdOjGfI hGdWHGY Je Ydi GdYde Ke Ydi GdWH Ke Ydi GdSjGSI Ke Ydi s
(3BNQgG (B:s
(3hGdKGfjI gi GdJjLGfjI aChd ef CONdJgG ehQJGf GdTjN eMeO GdMGaX hYfge CNP GdTjN GdUGdM eGdc GdPi gh TjN GdJjLGfjI ai ZQH GdSfZGd hBNQ OYhGfG Cf GdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3YdjgG bQGAI hJUMjMGJs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , JQeje s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdeYgO GdehQjJGfi ddHMK GdYdei (B((3JGQjN (B2728) s
Keywords: (3GdJGQjNs